Sociocultural barriers to outsourcing housework: Unraveling the non-use of domestic services - Miriam Trübner; Natascha Nisic (International Journal of Consumer Studies, 2024)
The outsourcing of housework is broadly recognized as providing an impetus for increasing women's participation in the labor market and relieving the burdens of households with children and dual earners. Despite an objective need, demand for paid domestic services is low, even for households with sufficient financial resources. By drawing on a German survey of cohabiting couples aged between 30 and 60, we analyze households that have, to date, not used domestic services (N0.167em=0.167em1479). Based on items about attitudes toward domestic services, we identify five distinct attitude profiles defined by diverse combinations and levels of sociocultural barriers to outsourcing housework, including gendered expectations, privacy concerns, aversion toward a servant culture, and trust and control issues. Our results establish that half of the sample exhibits scarcely any sociocultural aversion to the employment of domestic help. While some of these households report preferring to do housework within the family, households of higher social strata, in particular, express a need for external support, but are hindered by an insufficient supply of and access to appropriate paid domestic services. In contrast, the other half of the sample consists of subgroups of rejectors, revealing different levels of disapproval and normative-moral profiles concerning outsourcing. Interestingly, complete rejectors are often found in low-income households, indicating a strong connection between socioeconomic and sociocultural characteristics. The results highlight the potential for future developments within the domestic service sector to meet customers' normative and moral concerns.
Keywords: 330; attitude; domestic help; housework; make-or-buy; outsourcing